The PENGARUH SUPLEMENTASI PAKAN TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS PADA IKAN DAN RUMINANSIA - Putri, Dhifa Umairoh; Ningrum, Dinda Alithia; Syahfitri, Dinda; Panjaitan, Medisca; Siregar, Putri Naomi; Nababan, Wiwin Monalisa (Faculty of Animal Husbandry, University of Mataram, 2025)
The digestive system in animals plays a crucial role in nutrient utilization, supporting growth, productivity, and overall health. This study explores the effects of feed supplementation on fish and ruminants through a literature review, highlighting its impact on growth, survival, and productivity. Supplements such as inulin, turmeric, and Multi-Nutrient Sauce (MNS) have demonstrated their ability to improve feed efficiency, enhance gut health, and support organism development. In fish, inulin improves feed efficiency, promotes the growth of beneficial lactic acid bacteria and enhances overall growth, while turmeric improves survival rates, although its effect on growth is minimal. For ruminants, MNS supplementation optimizes digestion, metabolism, immunity, and productivity, contributing to increased weight gain and milk production. These findings highlight the potential of carefully tailored feed supplementation to enhance productivity and sustainability in aquaculture and livestock systems.